Dieta de morcegos filostomídeos (Mammalia, Chiroptera, Phyllostomidae) em fragmento urbano do Instituto São Vicente, Campo Grande, Mato Grosso do Sul - Martins, Mariana Pires Veiga; Torres, Jaire Marinho; Anjos, Elaine Aparecida Carvalho dos (Papéis Avulsos de Zoologia, 2014)
Due to their abundance and diversity, bats (Chiroptera) play an important ecological role in the ecosystem. The objective of this study was to report the diet of fruit bat species captured in fragments of the Instituto São Vicente, Campo Grande, MS. The study was carried out September 2011 and June. We captured 154 individuals belonging to 10 species, and the frugivorous were predominant. 41 fecal samples were collected, demonstrating the presence of pulp, seeds and traces of arthropods. The resources most used by bats were pioneer plants, evidenced by the predominance of seeds of Cecropia pachystachya, consumed by Artibeus lituratus. The results shows the importance of these animals for seed dispersal.